(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This research aims to analyze the dynamics of mergers, restructuring, and closures in the US International Broadcasting (USIB) sector from 1990 to 2025. USIB is a vital tool for US public diplomacy and foreign policy, encompassing established institutions such as Voice of America (VOA) and Radio Free Europe/Radio Liberty (RFE/RL). The significance of the research lies in the fact that these processes are not merely administrative adjustments, but rather reflect profound shifts in US foreign policy priorities, resource allocation strategies, and responses to the changing global media landscape. Historically, American international broadcasting has witnessed repeated debates and reforms, driven by perceptions of inefficiency or duplication, such as the Foreign Affairs Reform and Restructuring Act of 1998 and the National Defense Authorization Act of 2017. This research specifically examines the causes, processes, and outcomes of mergers and closures affecting major American international broadcasting entities (VOA, RFE/RL, RFA, MBN) from the end of the Cold War to the present(including the events of 2025). The research seeks to analyze how political, economic, strategic, and technological factors drove these changes and assess their impact on governance, editorial independence, and overall effectiveness.